Defibrillation lead placement using a transthoracic transatrial approach in a case without transvenous access due to lack of the right superior vena cava - Yosuke Otsuka (Journal of Arrhythmia, 2015)
A 65-year-old woman with a history of syncope was diagnosed with hypertrophic cardiomyopathy. She had previously undergone mastectomy of the left breast owing to breast cancer. Holter electrocardiogram (ECG) and monitor ECG revealed sick sinus syndrome (Type II) and non-sustained ventricular tachycardia. Sustained ventricular tachycardia and ventricular fibrillation were induced in an electrophysiological study. Although the patient was eligible for treatment with a dual chamber implantable cardioverter defibrillator (ICD), venography revealed lack of the right superior vena cava (R-SVC). Lead placement from the left subclavian vein would have increased the risk of lymphedema owing to the patient׳s mastectomy history. Consequently, the defibrillation lead was placed in the right ventricle by direct puncture of the right auricle through the tricuspid valve. The atrial lead was sutured to the atrial wall, and the postoperative course was unremarkable. Defibrillation lead placement using a transthoracic transatrial approach can be an alternative method in cases where a transvenous approach for lead placement is not feasible.